Trade and Religious Conversion in the Malay World: Study on Islamization in the Inderapura Kingdom in the 17 th - 18 th Centuries AD - Sudarman Sudarman; Awliya Rahmi; Urwatul Wusqo; Safrudin Halimy; Rahmawati Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
This study was derived from a paradegm developed by historians that the process of conversion to Islam in the Malay world was spread dominantly by the Sufis. As a result, historical reconstruction in this region has always been linked to the teachings, rituals and religious behavior of the Sufi. Based on available sources (manuscripts and archives), the role of traders was very significant in conversion to Islam in the Malay world. Through trade and religion, the countries in the Indian Ocean were interconnected. The religious conversion among traders grew faster as in the 17-18th century AD traders from various regions came to the West Coast of Sumatra to get spices. Most of these traders have embraced Islam. The Muslim traders carried the spirit of the Koran in their right hands and the commodities in the left hand. This spirit of spreading Islam was the driving force of the merchants to spread Islam in every place they visited. This research has implications for the community’s perspective on Islam in the Malay world because Islam that was brought by traders was progressive and flexible about the local culture. This study is a historical socio-religious study that is examined through three ap- proaches, namely historical approach, social approach, and religious approach. This study found that the religious conversion in the Malay world was succeeded mostly by the merchants. To facilitate the conversion, they married local women and negotiated with the authorized Sultan.